3.2.11 \(\int (b+2 c x) (-a+b x+c x^2)^p \, dx\)

Optimal. Leaf size=22 \[ \frac {\left (-a+b x+c x^2\right )^{p+1}}{p+1} \]

________________________________________________________________________________________

Rubi [A]  time = 0.01, antiderivative size = 22, normalized size of antiderivative = 1.00, number of steps used = 1, number of rules used = 1, integrand size = 21, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.048, Rules used = {629} \begin {gather*} \frac {\left (-a+b x+c x^2\right )^{p+1}}{p+1} \end {gather*}

Antiderivative was successfully verified.

[In]

Int[(b + 2*c*x)*(-a + b*x + c*x^2)^p,x]

[Out]

(-a + b*x + c*x^2)^(1 + p)/(1 + p)

Rule 629

Int[((d_) + (e_.)*(x_))*((a_.) + (b_.)*(x_) + (c_.)*(x_)^2)^(p_.), x_Symbol] :> Simp[(d*(a + b*x + c*x^2)^(p +
 1))/(b*(p + 1)), x] /; FreeQ[{a, b, c, d, e, p}, x] && EqQ[2*c*d - b*e, 0] && NeQ[p, -1]

Rubi steps

\begin {align*} \int (b+2 c x) \left (-a+b x+c x^2\right )^p \, dx &=\frac {\left (-a+b x+c x^2\right )^{1+p}}{1+p}\\ \end {align*}

________________________________________________________________________________________

Mathematica [A]  time = 0.01, size = 21, normalized size = 0.95 \begin {gather*} \frac {(x (b+c x)-a)^{p+1}}{p+1} \end {gather*}

Antiderivative was successfully verified.

[In]

Integrate[(b + 2*c*x)*(-a + b*x + c*x^2)^p,x]

[Out]

(-a + x*(b + c*x))^(1 + p)/(1 + p)

________________________________________________________________________________________

IntegrateAlgebraic [F]  time = 0.03, size = 0, normalized size = 0.00 \begin {gather*} \int (b+2 c x) \left (-a+b x+c x^2\right )^p \, dx \end {gather*}

Verification is not applicable to the result.

[In]

IntegrateAlgebraic[(b + 2*c*x)*(-a + b*x + c*x^2)^p,x]

[Out]

Defer[IntegrateAlgebraic][(b + 2*c*x)*(-a + b*x + c*x^2)^p, x]

________________________________________________________________________________________

fricas [A]  time = 0.82, size = 32, normalized size = 1.45 \begin {gather*} \frac {{\left (c x^{2} + b x - a\right )} {\left (c x^{2} + b x - a\right )}^{p}}{p + 1} \end {gather*}

Verification of antiderivative is not currently implemented for this CAS.

[In]

integrate((2*c*x+b)*(c*x^2+b*x-a)^p,x, algorithm="fricas")

[Out]

(c*x^2 + b*x - a)*(c*x^2 + b*x - a)^p/(p + 1)

________________________________________________________________________________________

giac [A]  time = 0.40, size = 22, normalized size = 1.00 \begin {gather*} \frac {{\left (c x^{2} + b x - a\right )}^{p + 1}}{p + 1} \end {gather*}

Verification of antiderivative is not currently implemented for this CAS.

[In]

integrate((2*c*x+b)*(c*x^2+b*x-a)^p,x, algorithm="giac")

[Out]

(c*x^2 + b*x - a)^(p + 1)/(p + 1)

________________________________________________________________________________________

maple [A]  time = 0.00, size = 23, normalized size = 1.05 \begin {gather*} \frac {\left (c \,x^{2}+b x -a \right )^{p +1}}{p +1} \end {gather*}

Verification of antiderivative is not currently implemented for this CAS.

[In]

int((2*c*x+b)*(c*x^2+b*x-a)^p,x)

[Out]

(c*x^2+b*x-a)^(p+1)/(p+1)

________________________________________________________________________________________

maxima [A]  time = 0.42, size = 22, normalized size = 1.00 \begin {gather*} \frac {{\left (c x^{2} + b x - a\right )}^{p + 1}}{p + 1} \end {gather*}

Verification of antiderivative is not currently implemented for this CAS.

[In]

integrate((2*c*x+b)*(c*x^2+b*x-a)^p,x, algorithm="maxima")

[Out]

(c*x^2 + b*x - a)^(p + 1)/(p + 1)

________________________________________________________________________________________

mupad [B]  time = 2.05, size = 42, normalized size = 1.91 \begin {gather*} \left (\frac {b\,x}{p+1}-\frac {a}{p+1}+\frac {c\,x^2}{p+1}\right )\,{\left (c\,x^2+b\,x-a\right )}^p \end {gather*}

Verification of antiderivative is not currently implemented for this CAS.

[In]

int((b + 2*c*x)*(b*x - a + c*x^2)^p,x)

[Out]

((b*x)/(p + 1) - a/(p + 1) + (c*x^2)/(p + 1))*(b*x - a + c*x^2)^p

________________________________________________________________________________________

sympy [B]  time = 56.66, size = 104, normalized size = 4.73 \begin {gather*} \begin {cases} - \frac {a \left (- a + b x + c x^{2}\right )^{p}}{p + 1} + \frac {b x \left (- a + b x + c x^{2}\right )^{p}}{p + 1} + \frac {c x^{2} \left (- a + b x + c x^{2}\right )^{p}}{p + 1} & \text {for}\: p \neq -1 \\\log {\left (\frac {b}{2 c} + x - \frac {\sqrt {4 a c + b^{2}}}{2 c} \right )} + \log {\left (\frac {b}{2 c} + x + \frac {\sqrt {4 a c + b^{2}}}{2 c} \right )} & \text {otherwise} \end {cases} \end {gather*}

Verification of antiderivative is not currently implemented for this CAS.

[In]

integrate((2*c*x+b)*(c*x**2+b*x-a)**p,x)

[Out]

Piecewise((-a*(-a + b*x + c*x**2)**p/(p + 1) + b*x*(-a + b*x + c*x**2)**p/(p + 1) + c*x**2*(-a + b*x + c*x**2)
**p/(p + 1), Ne(p, -1)), (log(b/(2*c) + x - sqrt(4*a*c + b**2)/(2*c)) + log(b/(2*c) + x + sqrt(4*a*c + b**2)/(
2*c)), True))

________________________________________________________________________________________